A preconditioning protocol and biaxial mechanical measurement of the small intestine. (1st January 2014) - Terry, Benjamin S.; Wang, Xin; Schoen, Jonathan A.; Rentschler, Mark E.
Understanding the biomechanical properties of the small intestine is necessary for developing in vivo mobility systems for miniature robots. In this work, we have experimentally determined preconditioning parameters and then performed in-plane biaxial biomechanical characterisation of small intestinal tissue. Excised tissue samples underwent uniaxial tension tests for two physiological Piola-stress values and multiple cycles. The percent change in the length of the tissue reached equilibrium after approximately 13 preconditioning cycles for both loading values. The mechanical behaviour of the tissue did not appear to be affected by the loading values. Thirty-three tissue samples from the proximal, middle, and distal regions of the small intestine of three pigs underwent preconditioning and subsequent in-plane biaxial biomechanical characterisation. The mean moduli for all samples in the low and high modulus regions were, respectively, 307.25 ± 29.67 kPa and 2, 211.72 ± 316.88 kPa along the longitudinal direction, and 180.07 ± 17.01 kPa and 1, 388.89 ± 206.15 kPa along the circumferential direction. For the low modulus region, the proximal tissue was significantly stiffer than the distal tissue in the circumferential direction ( p = 0.0356). Overall, the longitudinal direction was stiffer for both the high and low modulus regions ( p = 0.0056 and 0.0004, respectively).